1965
DOI: 10.1063/1.1697204
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of Complex Ions in the Aqueous ZnO–KOH System

Abstract: Proton magnetic resonance measurements of the aqueous ZnQ-KOH system have been made. Only a single resonance line is observed, but the position of the line depends on the concentrations of KOH and ZnO. Analysis of the data is consistent with the presence of only one zincate species. A value for the chemical shift of the zincate ion is derived, and also a more precise value for the chemical shift of KOH in water is determined. The significance of the results is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 16 publications
0
40
0
Order By: Relevance
“…By emf measurements, Dirkse has shown that this species is the complex tetrahydroxyl anion, Zn(OH)4--, an interpretation supported by recent Raman and infrared, as well as NMR, studies (2,4,5).…”
Section: General Electric Research and Development Center Schenectadmentioning
confidence: 85%
“…By emf measurements, Dirkse has shown that this species is the complex tetrahydroxyl anion, Zn(OH)4--, an interpretation supported by recent Raman and infrared, as well as NMR, studies (2,4,5).…”
Section: General Electric Research and Development Center Schenectadmentioning
confidence: 85%
“…The very short-lived potential plateau, observed at high current densities, may well be indicative of this step. This stage is followed by equilibria Zn (OH) 2ad ~ Zn (OH) 2diss [5] Zn(OH) 2diss -F-n OH-~ Zn (OH)2+,, [6] If either [5] or [6] is rate controlling, and if a firstorder process, then, assuming the validity of [3] and [4], kf and kr may be calculated using the data of Table IV. In potassium hydroxide, k I = 0.98, kr ~ 0.9 sec -1.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical shifts of ZnO dissolved in different ratios of KOH to ZnO have been studied [109]. Due to very rapid chemical exchange among the proton containing species, only one sharp peak was observed.…”
Section: Agreement Between Experimental and Calculated Values Of The mentioning
confidence: 99%